Optimization of the Proportion of Surfactant, Co-Surfactant, and Candlenut Oil for Self-Nanoemulsifying Drug Delivery System (SNEDDS) of Secang Heartwood (Caesalpinia sappan L.) Methanolic Extract - Anif Nur Artanti; Fea Prihapsara; Dian Eka Ermawati; Nugraha Mas'ud (UNIVERSITAS SEBELAS MARET (UNS), 2021)
This study aimed to determine the optimum proportion of hazelnut oil, surfactants, and cosurfactants for SNEDDS of Secang Heartwood using the simplex lattice design (SLD) method using the Design-Expert software. The SNEDDS formula was prepared using Tween 80 and Croduret 50 ss as surfactants, propylene glycol as cosurfactant, and candlenut oil based on physical stability parameters: formula transmittance (%), separation phase, and emulsification time. The optimum SNEDDS formula was compared with the predictive value [p> 0.05] provided by the SLD; then extract the loading dose, accelerated stability test, analysis of particle size, and zeta potential. The optimum proportion of Tween 80-Croduret 50 ss, propylene glycol, and hazelnut oil, based on the SLD, was 62.43%; 22.57%; and 15.0%. The results showed that the transmittance was 93.2%; emulsification time was 74.67 seconds, and; separation phase was 0.89. The SLD's predictive values of the transmittance percentage, emulsification time, and separation phase were 94.98%, 78.97 seconds, 0.84, respectively. The results of the one-sample t-test statistical analysis showed no significant difference between the observative and predictive results. SNEDDS was found capable of loading 25.0 mg of secang heartwood methanolic extract in each system, with a particle size of 23.2 nm, a polydispersity index of 0.142, and zeta potential of +20.8 mV.